2020
DOI: 10.1111/bjet.13025
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary resuscitation training for high school students using an immersive 360‐degree virtual reality environment

Abstract: Cardiopulmonary resuscitation (CPR) is a lifesaving emergency procedure. To increase survival rates, it is recommended to increase the number of high school students who know how to perform CPR. We have developed an immersive "Virtual Reality (VR) Resuscitation Training" to train the theoretical knowledge of CPR in which trainees must save the life of the patient in a virtual environment. This paper presents a randomized controlled study with a pre-posttest design to explore whether a VR enhanced curriculum im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…This immersive and realistic VR environment facilitates memorizing stepwise procedures more efficiently [ 25 ]. Additionally, our results showed that frequent practice and increased exposure in the CPVR-sim is valuable since it refreshes the knowledge and gives the clinician more confidence in taking the lead in future situations, which is in line with previous studies [ 8 , 9 , 12 , 13 ]. This is especially important in infrequent CPR cases with emergency resternotomy, which occurs only a few times per year.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This immersive and realistic VR environment facilitates memorizing stepwise procedures more efficiently [ 25 ]. Additionally, our results showed that frequent practice and increased exposure in the CPVR-sim is valuable since it refreshes the knowledge and gives the clinician more confidence in taking the lead in future situations, which is in line with previous studies [ 8 , 9 , 12 , 13 ]. This is especially important in infrequent CPR cases with emergency resternotomy, which occurs only a few times per year.…”
Section: Discussionsupporting
confidence: 89%
“…However, the paucity of cardiac arrest after cardiac surgery limits the possibilities of clinical training for clinicians [ 8 ]. CPR training allows clinical staff to acquire theoretical knowledge on the protocol, together with the ability to physically perform the steps described within the protocol [ 9 ]. This is commonly taught in instructor-led training sessions, requiring multiple team members and resources [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future developments in virtual and augmented reality simulation technologies may soon help improve the provision of layperson CPR and AED training, and facilitate realistic refresher training on demand. 19. , 20.…”
mentioning
confidence: 99%
“…The students who used IVR also provided significantly higher cognitive, behavioural, emotional and social engagement ratings with respect to the science modules, as well as generally high usefulness and usability ratings of the IVR technology. Barsom et al (2020) investigated high school students' use of 360-degree video to learn cardiopulmonary resuscitation (CPR), finding that it led to significantly higher increase in theoretical CPR knowledge compared to a standard e-learning group as well as a significantly higher gain in knowledge relating to sequence of CPR steps. The immersive approach enabling the participants to explore the realistic environment in any direction aimed to overcome the gap between traditional classroom training and real-life application, to increase by-stander response during cardiac arrest.…”
mentioning
confidence: 99%